LEXICAL STYLISTIC TOOLS. METHOPHORA, METONYMY, IRONY, EPITHET. (Лучшие интеллектуальные исследования, 2025)
Abstract: Lexical stylistic tools occupy an important place in literature and the art of speech. They increase the expressive power of language, allowing for a more vivid and touching conveyance of thoughts. Within the tools of lexical Stylistics, such concepts as methophora, metonymy, irony and epithet are of particular importance. Each of them is characterized by its own characteristics and methods of application, so it is necessary to study and understand them more deeply.